Fostering Creativity Through Play: Innovative Learning Development at Sunshine Daycare UNESA - Eka Cahya Maulidiyah; Rachma Hasibuan; Sri Setyowati; Muhammad Reza; Afifah Rahmaningrum; Fatiha Khoirotunnisa Elfahmi; Melia Dwi Widayanti; Dhian Gowinda Luh Safitri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2026)
As the number of full-time working parents continues to rise, so does the demand for high-quality daycare services. However, many daycare centers still lack structured learning programs that support the holistic development of young children. This study responds to that gap by developing a creative learning model grounded in play-based learning, specifically designed for caregivers at Sunshine Daycare, an early childhood center under the management of the Early Childhood Education Department (PG-PAUD), UNESA. Using the ADDIE model within a Research and Development (R&D) framework, data were collected through observations and interviews with caregivers and parents. The results reveal that implementing play-based creative learning empowers caregivers to plan engaging daily activities and signature programs that foster children's development across multiple domains: language, cognitive, motor, moral-religious, and socio-emotional. These findings underscore the urgency of integrating structured, child-centered approaches in daycare settings to ensure purposeful and developmentally appropriate learning experiences.